Factors Influencing the Incidence of Hypothermia in Spinal Anesthesia Patients at the Central Surgery Installation of Islamic Fatimah Hospital, Cilacap - Paramadinah, Elsha; Tri Yudono, Danang; Kumala Dewi, Feti (Viva Medika, 2023)
The patient’s care body temperature below 36°C is usually diagnosed as hypothermia. The human thermoregulatory system maintains metabolic activity by keeping body temperature about 37ºC. Hypothermia is linked to anesthesia and surgery. This study examines the risk factors for hypothermia in spinal anesthesia patients at the Central Surgical Installation of RSI Fatimah Cilacap. Age, gender, BMI, and length are variables. This research method is using a quantitative analytical observational approach with total sampling technique. The results of this study showed that the most dominant age of respondents was adults 25-46 years (45.9%) with mild hypothermia (29.7%). The study also found 59.5% of participants were female and 29.7% had mild or moderate hypothermia. Most respondents (64.9%) had an average BMI 37.8% had mild hypoyhermia. Finally, 56.8% of respondents had 1-2-hour surgery, with 32.4% experiencing mild hypothermia. The conclusion of this study found that Body Mass Index (BMI) is the main risk factor for hypothermia with 64.9% of people having a normal BMI.